MEMS-based material corrosion electrochemical measurement sensor and preparation method thereof, and material corrosion electrochemical measurement equipment
Through the MEMS-based material corrosion electrochemical measurement sensor, combined with the combination of working electrode-assistive electrode module and reference electrode module and silicon-silicon bonding method, the existing sensors have large size, high power consumption and poor stability, and the miniaturized, low-cost and high-sensitivity material corrosion electrochemical measurement sensor is achieved, which is suitable for large-scale applications and batch manufacturing.
Patent Information
- Application Number
- CN202411875685.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-19
AI Technical Summary
Existing material corrosion sensors have large volume, high power consumption, poor stability and low response sensitivity, which limit the large-area application of material corrosion sensors and the development of material corrosion genetic engineering technology.
Using a material corrosion electrochemical measurement sensor based on MEMS, a miniaturized and low-cost corrosion electrochemical three-electrode system is formed by combining the working electrode-assisted electrode module and the reference electrode module and the silicon-silicon bonding method.
It has achieved a miniaturized and low-cost material corrosion electrochemical measurement sensor, which has high sensitivity and stability, and is suitable for large-scale integrated and batch manufacturing, meeting the online monitoring needs of corrosion electrochemical for different specifications and materials.
Smart Images

Figure CN119666718A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of material corrosion sensors, and in particular to a material corrosion electrochemical measurement sensor based on MEMS, a preparation method thereof, and a material corrosion electrochemical measurement device. Background Art
[0002] The natural environmental corrosion of materials is very complex, with many influencing factors, and it is difficult to simulate in the laboratory. Only through long-term continuous field tests and observations at field test sites can we obtain corrosion data that conforms to reality. High-throughput corrosion data collection and analysis and mining of environmental corrosion failure of materials has always been a cutting-edge hot issue. Related work has a history of hundreds of years, and electrochemical resistance sensors, inductance sensors, galvanic sensors, AC impedance sensors, etc. have been established, and related data accumulation and mining and analysis work has been carried out. The corresponding sensor technology is mainly based on structural and solid sensors, and the application of such sensors in the field is very limited. Therefore, in order to deploy material sensors on a large scale and obtain material corrosion data, it is necessary to have smaller size, low cost, low power consumption and device-level material corrosion sensors.
[0003] Micro-Electro-Mechanical System (MEMS) material corrosion chip and sensor is an intelligent micro-electromechanical sensor system that can monitor the environmental corrosion rate of materials and perform artificial intelligence processing and analysis on environmental corrosion data. The sensor system is equipped with MEMS material intelligent corrosion chip and embedded ASIC data processing chip. Compared with traditional sensors, it has the characteristics of small size, light weight, low cost, high reliability, suitable for mass production, easy integration and intelligent realization. In recent years, MEMS sensor and artificial intelligence data mining technology have developed rapidly, but there is no micro-electromechanical system and corresponding corrosion chip development technology for the process of material service failure evaluation. Traditional sensors have the characteristics of large size, high power consumption, poor stability and low response sensitivity, which seriously hinder the large-scale application of material corrosion sensors and the development of material corrosion genetic engineering technology. In the field of material corrosion sensors, realizing chip-level material corrosion sensors, reducing monitoring costs and improving monitoring accuracy has always been a difficult problem in the field of corrosion, and it is also the international academic frontier and technical competition focus in the field of material corrosion genetic engineering research. The key lies in the development of MEMS material corrosion chips and sensors to realize the in-situ real-time high-throughput online collection and mining analysis of corrosion data in the process of material service failure evaluation. Summary of the invention
[0004] The purpose of the present application is to provide a MEMS-based material corrosion electrochemical measurement sensor and a preparation method thereof and a material corrosion electrochemical measurement device to solve the above-mentioned problems.
[0005] To achieve the above objectives, this application adopts the following technical solutions: A material corrosion electrochemical measurement sensor based on MEMS, comprising: A working electrode-auxiliary electrode module, wherein the working electrode-auxiliary electrode module comprises a first silicon substrate, a working electrode and an auxiliary electrode, wherein the first silicon substrate is provided with a recessed portion, wherein the working electrode is provided on one side of an inner wall and a bottom of the recessed portion, wherein the auxiliary electrode is provided on the other side of an inner wall and a bottom of the recessed portion, wherein the working electrode, the auxiliary electrode and the recessed portion form an accommodation space; A reference electrode module, the reference electrode module comprising a second silicon substrate and a reference electrode, the reference electrode being arranged on one side of the second silicon substrate and forming a convex portion, and the second silicon substrate having a through hole along a thickness direction; The protrusion is arranged in the accommodating space, the working electrode, the auxiliary electrode and the reference electrode are not connected to each other, and the first silicon substrate and the second silicon substrate are fixedly connected; The spacing between the working electrode and the reference electrode is 1000-2000μm (can be 1000μm, 1100μm, 1200μm, 1300μm, 1400μm, 1500μm, 1600μm, 1700μm, 1800μm, 1900μm, 2000μm or any value between 1000-2000μm), and the spacing between the working electrode and the auxiliary electrode is 1000-5000μm (can be 1000μm, 1500μm, 2000μm, 2500μm, 3000μm, 3500μm, 4000μm, 4500μm, 5000μm or any value between 1000-5000μm).
[0006] The corrosion electrochemical three-electrode system after connection should comply with the measurement rules of corrosion electrochemistry, that is, the stacking order of working electrode-reference electrode-counter electrode should be met, and the working electrode and the reference electrode should be as close as possible to reduce the ohmic resistance during the corrosion electrochemical measurement process.
[0007] Preferably, the working electrode and the auxiliary electrode have L-shaped cross-sections.
[0008] Preferably, the working electrode, the auxiliary electrode and the reference electrode are made of the target metal material to be measured.
[0009] Preferably, the accommodating spaces and the protruding portions are provided in multiple pairs.
[0010] The present application also provides a method for preparing a material corrosion electrochemical measurement sensor based on MEMS, comprising: Applying a first semiconductor photoresist to one side of the first silicon substrate and performing a first soft bake, then using an electrolytic cell mask to expose, develop, and dissolve under corresponding ultraviolet light to form an exposed substrate area; etching the exposed substrate area by ion etching to obtain the recessed portion; Residues of the first semiconductor photoresist are removed, a second semiconductor photoresist is applied to the side of the first silicon substrate having the recessed portion and a second soft bake is performed, and then a working electrode mask is used to expose, develop, and dissolve under corresponding ultraviolet light to form a working electrode pattern; a target metal material to be tested is used to form a working electrode layer at the position of the working electrode pattern by sputtering or electroplating; Removing the residual second semiconductor photoresist and metal material to obtain the working electrode; Applying a third semiconductor photoresist to the side of the first silicon substrate having the recessed portion and performing a third soft baking, then using an auxiliary electrode mask to perform exposure, development, and dissolution under corresponding ultraviolet light to form an auxiliary electrode pattern; using a target metal material to be tested to form an auxiliary electrode layer at the position of the auxiliary electrode pattern by sputtering or electroplating; Removing the residual third semiconductor photoresist and metal material to obtain the auxiliary electrode; that is, obtaining the working electrode-auxiliary electrode module; A reference electrode layer is provided on one side surface of the second silicon substrate by sputtering or electroplating, and then a fourth semiconductor photoresist is coated and a fourth soft baking is performed, and then an auxiliary electrode mask is used to expose, develop, and dissolve under corresponding ultraviolet light to form a reference electrode pattern; etching at the position of the reference electrode pattern by ion etching to remove the residual fourth semiconductor photoresist and metal material to obtain the reference electrode; A fifth semiconductor photoresist is coated on a side of the second silicon substrate away from the reference electrode and a fifth soft baking is performed, and then a through-hole mask is used to expose, develop, and dissolve under corresponding ultraviolet light to form a through-hole pattern; the through-hole is obtained by etching at the position of the through-hole pattern by ion etching; that is, the reference electrode module is obtained; The working electrode-auxiliary electrode module and the reference electrode module are silicon-silicon bonded to obtain the MEMS-based material corrosion electrochemical measurement sensor.
[0011] Preferably, the first silicon substrate and the second silicon substrate are cleaned before use.
[0012] Preferably, the temperatures of the first soft baking, the second soft baking, the third soft baking, the fourth soft baking and the fifth soft baking are independently 90-110° C.
[0013] Preferably, before the silicon-silicon bonding, the first silicon substrate and the second silicon substrate are surface cleaned; The silicon-silicon bonding is performed by heating and annealing.
[0014] The present application also provides a material corrosion electrochemical measurement device, including the MEMS-based material corrosion electrochemical measurement sensor. Preferably, the material corrosion electrochemical measurement device further comprises a substrate lead frame; The working electrode, the auxiliary electrode, and the reference electrode are electrically connected to the substrate lead frame.
[0015] Compared with the prior art, the beneficial effects of this application include: The MEMS-based material corrosion electrochemical measurement sensor provided in the present application combines a working electrode-auxiliary electrode module with a reference electrode module, and forms a three-electrode system for electrochemical measurement of material corrosion by a bonding method. The sensor has the characteristics of miniaturization and low cost, and the preparation method is mature, which can be convenient for large-scale integration and batch manufacturing, and can meet the needs of online monitoring of moisture or liquid phase corrosion electrochemistry of different specifications and materials. The width of the electrolytic cell (depression) should be greater than the width of the reference electrode to ensure that the reference electrode can be smoothly placed in the electrolytic cell groove; the number, size, and position of the electrolytic cell can be adjusted according to actual needs, and the number of three-electrode systems can also be adjusted according to actual needs. The working electrode, reference electrode, and auxiliary electrode can be replaced according to the actual material corrosion electrochemical measurement requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0017] Figure 1 A schematic diagram of the preparation process of the working electrode-auxiliary electrode module provided in the embodiment; Figure 2 A schematic diagram of the preparation process of the reference electrode module provided in the embodiment; Figure 3 A schematic diagram of bonding of a MEMS-based material corrosion electrochemical measurement sensor provided in an embodiment; Figure 4 A schematic diagram of a substrate lead frame provided in an embodiment; Figure 5 A top view of a material corrosion electrochemical measurement device provided for an embodiment; Figure 6 A perspective view of a material corrosion electrochemical measurement device provided for an embodiment; Figure 7 The open circuit potential test result diagram of the sensor obtained in the embodiment; Figure 8 The electrochemical impedance spectroscopy test results of the sensor obtained in the embodiment are shown in FIG. Fig. 9 This is a diagram of the weak polarization test results of the sensor obtained in the embodiment; Fig.10 This is a graph showing the electrochemical impedance test results of the sensor obtained in Comparative Example 1; Fig.11 This is a graph showing the electrochemical impedance test results of the sensor obtained in Comparative Example 2.
[0018] Reference numerals: 1-first silicon substrate; 2-second silicon substrate; 3-working electrode; 4-auxiliary electrode; 5-reference electrode; 6-electrolytic cell; 7-substrate lead frame; 8-bonding wire; 9-pad; 10-through hole. DETAILED DESCRIPTION
[0019] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0020] Example This embodiment provides a corrosion electrochemical measurement sensor based on MEMS material, and its preparation process is as follows: like Figure 1 As shown, (1) the preparation process of the auxiliary electrode and the working electrode is as follows: 1.1 A silicon wafer with a diameter of 100 mm and a thickness of 525 μm was used as the first substrate silicon wafer. First, the surface of the first substrate silicon wafer was cleaned with deionized water; then, the silicon wafer was cleaned with a cleaning solution composed of 25% hydrogen peroxide, 25% ammonia water and pure water in a volume ratio of 1:1:20, and the cleaning time was about 270 seconds; then, a cleaning solution composed of 30% hydrochloric acid, 25% hydrogen peroxide and pure water in a volume ratio of 1:1:20 was used to continue cleaning for 250 seconds; then, a large amount of deionized water was used to rinse the silicon wafer, and a high-speed spin-drying device was used to dry the silicon wafer, and the spin-drying process time was 290-310 seconds.
[0021] 1.2 Use SU-8 semiconductor UV photoresist to coat the silicon wafer. Spin the SU-8 photoresist component on the substrate at a speed of 1200r / min. The spin coating thickness is controlled at 180 microns. Use a uniform heating plate to heat the silicon wafer at 100℃ for 100s to fully dry it and then transfer it to the photolithography machine. Load the mask of the electrolytic cell onto the photolithography machine for photolithography development. The UV radiation dose is 200mJ / cm 2 Make a 6-12 second exposure.
[0022] After 1.3, fully develop with SU-8 developer until the corrosion electrolytic cell pattern is clearly and completely presented; 1.4 After that, the silicon wafer is etched by a femtosecond laser etching method to remove the exposed substrate area, and an electrolytic cell of the corrosion electrolyte is etched downward in the exposed substrate area as an electrolytic cell for the corrosion electrochemical three-electrode reaction. The etching rate is about 8μm / min and the total etching depth is 200μm.
[0023] 1.5 Repeat step 1.1 to remove the remaining photoresist on the silicon wafer, then rinse with deionized water and dry for later use; 1.6 Repeat steps 1.2 to 1.4. The difference between the steps is that the mask used in this step is the mask of the working electrode. After exposure and development, the pattern of the working electrode area is dissolved to form the pattern of the working electrode in the electrolytic cell; 1.7 The working electrode required for the electrochemical measurement of material corrosion is formed by magnetron sputtering. In this example, the working electrode uses metal copper as the target material of magnetron sputtering, which also serves as the anode of the electrochemical measurement of material corrosion. The sputtering thickness is about 20 μm. 1.8 Repeat step 1.1 to remove the residual photoresist and the magnetron sputtered working electrode material on the first substrate silicon wafer, and then wash with deionized water and dry for later use; 1.9 Repeat steps 1.2 to 1.4. The difference between the steps is that the mask used in this step is the mask of the auxiliary electrode. After exposure and development, the pattern of the auxiliary electrode area is dissolved to form the pattern of the auxiliary electrode in the electrolytic cell; 1.10 The auxiliary electrode required for electrochemical measurement of material corrosion is prepared by magnetron sputtering. In this example, Pt target material is used and the sputtering thickness is about 20 μm; 1.11 Repeat step 1.1 to remove the residual photoresist on the wafer and the sputtered auxiliary electrode material on the photoresist, then rinse with deionized water and dry for later use. In this way, the electrolytic cell, working electrode and auxiliary electrode on the first substrate have been successfully prepared.
[0024] like Figure 2 As shown, (2) the preparation process of the reference electrode is as follows: 2.1 A silicon wafer with a diameter of 100 mm and a thickness of 525 μm was used as the second substrate silicon wafer. First, the surface of the second substrate silicon wafer was cleaned with deionized water; then, the silicon wafer was cleaned with a cleaning solution composed of 25% hydrogen peroxide, 25% ammonia water and pure water in a volume ratio of 1:1:20, and the cleaning time was about 260 seconds; then, a cleaning solution composed of 30% hydrochloric acid, 25% hydrogen peroxide and pure water in a volume ratio of 1:1:20 was used to continue cleaning for 250 seconds; then, a large amount of deionized water was used to rinse the silicon wafer, and a high-speed spin drying device was used to dry the silicon wafer, and the spin drying process time was 290 seconds; 2.2 The reference electrode required for electrochemical measurement of material corrosion is prepared by magnetron sputtering. In this example, Ag reference electrode is used; 2.3 SU-8 semiconductor UV photoresist was used to coat the silicon wafer. The SU-8 photoresist component was spin-coated on the substrate at a speed of 1200 r / min. The spin coating thickness was controlled at 180 μm. The silicon wafer was heated at 100 °C for 100 s using a uniform heating plate and fully dried. After that, it was transferred to the photolithography machine and the mask of the reference electrode was loaded on the photolithography machine for photolithography development. The UV radiation dose was 200 mJ / cm 2 Take a 10 second exposure.
[0025] 2.4 After that, use SU-8 developer to fully develop until the reference electrode pattern is clearly and completely presented; 2.5, the silicon wafer is etched by deep silicon etching method to remove the exposed substrate area, and a groove is etched downward in the exposed substrate area to serve as a reference electrode for the three-electrode reaction. The etching rate is about 8μm / min and the total etching depth is 200μm.
[0026] 2.6 Repeat step 1.1 to remove the remaining photoresist on the silicon wafer, then wash it with deionized water and dry it for later use; in this way, the Ag reference electrode is prepared.
[0027] 2.7 Coat the semiconductor photoresist on the side of the second substrate silicon wafer away from the reference electrode and perform soft baking. Coat the silicon wafer with SU-8 semiconductor UV photoresist. Spin the SU-8 photoresist component on the substrate at a speed of 1200r / min. The spin coating thickness is controlled at 180 microns. Heat the silicon wafer at 100℃ for 100s using a uniform heating plate to fully dry it and then transfer it to the photolithography machine. Load the through-hole mask onto the photolithography machine for photolithography development. The UV radiation dose is 200mJ / cm 2 Take a 10 second exposure.
[0028] After 2.8, use SU-8 developer to fully develop and present the through-hole pattern completely and clearly; 2.9 Etching the silicon wafer by a deep silicon etching method to remove the exposed substrate area, and etching a through hole downward in the exposed substrate area; 2.10 Repeat step 1.1 to remove the remaining photoresist on the silicon wafer, then rinse with deionized water and dry for later use; in this way, a through hole is obtained.
[0029] (3) Silicon-silicon bonding 3.1 Silicon-silicon bonding is performed on the first substrate silicon wafer with a working electrode, an auxiliary electrode and an electrolytic cell and the second substrate silicon wafer with a reference electrode. Before bonding, the first substrate silicon wafer and the second substrate silicon wafer are first cleaned by RCA process to increase the surface electrostatic tension of the silicon wafer; the component A solution in the RCA process is prepared, which is a mixture of ammonia water, hydrogen peroxide and water (ammonia water: H2O2: H2O=1:1:6), heated to 80 degrees Celsius, and the substrate silicon wafer is immersed in the component A solution for 15 minutes, then taken out and removed by deionization. Rinse with deionized water; prepare the B component solution in the RCA process, which is a mixture of hydrochloric acid, hydrogen peroxide and water (HCl:H2O2:H2O=1:1:5); soak the substrate silicon wafer in the B component solution for 15 minutes, then take it out and rinse it with deionized water; then, rinse the two cleaned substrate silicon wafers in a 2% diluted HF solution for 30 seconds to completely remove the intrinsic oxide layer on the substrate silicon wafer, then rinse with deionized water and dry, and completely bond the two substrate silicon wafers together at room temperature to ensure that the bonding surface is flat and free of impurities; 3.2 As Figure 3 As shown, after high-temperature annealing at 250°C, a physical and chemical reaction occurs at the silicon-silicon bonding interface to form a chemical covalent bond connection, thereby enhancing the bonding strength so that the first substrate and the second substrate form a whole, the unbonded rate is less than 0.5%, and the bonding strength is greater than 15MPa.
[0030] The obtained corrosion electrochemical sensor comprises: a working electrode-auxiliary electrode module and a reference electrode module; The working electrode-auxiliary electrode module includes a first silicon substrate 1, which is provided with a recessed portion; the reference electrode module includes a second silicon substrate 2; the first silicon substrate 1 and the second silicon substrate 2 are fixedly connected. The working electrode 3 is arranged on the left side of the inner wall and the left side of the bottom of the recessed portion, and is L-shaped as a whole; the auxiliary electrode 4 is arranged on the right side of the inner wall and the right side of the bottom of the recessed portion, and is L-shaped as a whole; the working electrode 3, the auxiliary electrode 4 and the recessed portion form a containing space; the reference electrode 5 is arranged on one side of the second silicon substrate 2 and forms a convex portion, the reference electrode 5 is arranged in the containing space, and the working electrode 3, the auxiliary electrode 4 and the reference electrode 5 are not connected to each other. The recessed portion serves as an electrolytic cell 6.
[0031] This embodiment also provides a material corrosion electrochemical measurement device, including the above-mentioned material corrosion electrochemical measurement sensor based on MEMS and a substrate lead frame 7 (such as Figure 4 As shown); bonding wires 8 are arranged on the substrate lead frame 7, and each bonding wire 8 is connected to the working electrode 3, the auxiliary electrode 4, and the reference electrode 5 respectively.
[0032] The preparation method includes: - wire bonding: 4.1 Design a copper-nickel alloy substrate lead frame 7 suitable for MEMS corrosion electrochemical measurement. Cut the bonded silicon wafer and place it on the frame. To ensure the bonding quality between the frame and the working electrode 3, auxiliary electrode 4 and reference electrode 5 on the silicon wafer, use a plasma cleaning device before bonding. Use 200W power for 10 seconds at an argon flow rate of 10ml / min to achieve ion cleaning of the silicon wafer and the frame. 4.2 The copper wire bonding process is used to precisely weld the working electrode 3, the auxiliary electrode 4 and the reference electrode 5 to the copper-nickel alloy substrate lead frame 7 on the pad 9 to achieve electrical interconnection between the MEMS chip and the substrate and information exchange between the chips.
[0033] like Figure 5 and Figure 6 As shown, the second silicon substrate has two through holes 10 along the thickness direction for flowing fluid medium such as electrolyte into the electrolytic cell 6 .
[0034] 5. Sensor Test 5.1 The sensor of this example was placed in a high and low temperature alternating humidity chamber for electrochemical testing. The test contents included electrochemical open circuit potential, electrochemical AC impedance and weak polarization test. During the test, the humidity was controlled at 100% and the temperature was controlled at 25 degrees Celsius. Before the test, the system was placed in a stable state for 2 hours. The open circuit potential test time was 1200s. The results are as follows: Figure 7 As shown; the AC impedance scanning frequency is 0.01Hz~100kHz, the applied interference voltage is 10mV, and the AC impedance results are as follows Figure 8 As shown, the polarization potential test is a relative reference potential ±10mV scan, the scanning frequency is 0.1667Hz, and the results are as follows Fig. 9 shown.
[0035] In this embodiment, the coordinated corrosion electrochemical three-electrode system should be arranged in the order of working electrode, reference electrode and auxiliary electrode, where the spacing between the working electrode and the reference electrode is 2000μm. If the distance is too close, a charge shielding effect will occur, affecting the progress of the corrosion electrochemical reaction; if it is too far, a large ohmic drop will be generated, directly affecting the accuracy of the electrochemical measurement; at the same time, the working electrode and the auxiliary electrode are consistent in shape and arranged oppositely, with a spacing of 4000μm, to form a good charge loop, fully ensuring the accuracy of the corrosion electrochemical measurement. For this reason, this patent proposes a comparative example to measure the AC impedance, fully considering the influence of electrode position and electrode spacing on the corrosion electrochemical measurement during the corrosion electrochemical measurement process.
[0036] Comparative Example 1 The difference from the embodiment is that the spacing between the working electrode and the reference electrode is controlled to be 500 μm, and the spacing between the working electrode and the auxiliary electrode is still maintained at 4000 μm. The electrochemical impedance measurement is carried out according to the corrosion electrochemical measurement method in the embodiment. The results are as follows: Fig.10 As shown, Fig.10 The measured electrochemical impedance increased significantly, mainly because the gap was too small, which produced an electrochemical shielding effect on the one hand, and on the other hand, the gap was too small, which affected the penetration of the solution when the electrostatic tension effect decreased. Comparative Example 2 The difference from the embodiment is that the order of the working electrode, the reference electrode and the auxiliary electrode is controlled to be the working electrode, the auxiliary electrode and the reference electrode. The distance between the working electrode and the reference electrode is 4000 μm, the distance between the working electrode and the auxiliary electrode is 2000 μm, and the electrochemical impedance is measured according to the corrosion electrochemical measurement method in the embodiment. The results are as follows: Fig.11 As shown, Fig.11 The impedance value corresponding to the low-frequency part of the measured electrochemical impedance has increased significantly, indicating that there is a large ohmic drop in the system. The ohmic drop is caused by the distance between the working electrode and the reference electrode being too far. When the perturbation potential applied to the working electrode is used for impedance measurement, the actual applied potential is greatly reduced due to the existence of the ohmic drop. The corrosion electrochemical measurement sensor based on MEMS material provided in this application has the characteristics of miniaturization and low cost, and the preparation method is mature, which can be convenient for large-scale integration and batch manufacturing, and can meet the needs of online monitoring of corrosion electrochemistry of different specifications and different materials.
[0037] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A material corrosion electrochemical measurement sensor based on MEMS, characterized in that: include: A working electrode-auxiliary electrode module, wherein the working electrode-auxiliary electrode module comprises a first silicon substrate, a working electrode and an auxiliary electrode, wherein the first silicon substrate is provided with a recessed portion, wherein the working electrode is provided on one side of an inner wall and a bottom of the recessed portion, wherein the auxiliary electrode is provided on the other side of an inner wall and a bottom of the recessed portion, wherein the working electrode, the auxiliary electrode and the recessed portion form an accommodation space; A reference electrode module, the reference electrode module comprising a second silicon substrate and a reference electrode, the reference electrode being arranged on one side of the second silicon substrate and forming a convex portion, and the second silicon substrate having a through hole along a thickness direction; The protrusion is arranged in the accommodating space, the working electrode, the auxiliary electrode and the reference electrode are not connected to each other, and the first silicon substrate and the second silicon substrate are fixedly connected; The distance between the working electrode and the reference electrode is 1000-2000 μm, and the distance between the working electrode and the auxiliary electrode is 1000-5000 μm.
2. The MEMS-based material corrosion electrochemical measurement sensor according to claim 1, characterized in that: The working electrode and the auxiliary electrode have L-shaped cross sections.
3. The MEMS-based material corrosion electrochemical measurement sensor according to claim 1, characterized in that: The working electrode, the auxiliary electrode and the reference electrode are prepared by using the target metal material to be tested.
4. The MEMS-based material corrosion electrochemical measurement sensor according to any one of claims 1 to 3, characterized in that: The accommodating spaces and the protruding portions are provided in pairs.
5. A method for preparing a material corrosion electrochemical measurement sensor based on MEMS, characterized in that: include: Applying a first semiconductor photoresist to one side of the first silicon substrate and performing a first soft bake, and then using an electrolytic cell mask to expose, develop, and dissolve under corresponding ultraviolet light to form an exposed substrate area; Etching the exposed substrate region to obtain the recessed portion by ion etching; Removing the residual first semiconductor photoresist, applying a second semiconductor photoresist to the side of the first silicon substrate having the recessed portion and performing a second soft bake, and then using a working electrode mask to perform exposure, development, and dissolution under corresponding ultraviolet light to form a working electrode pattern; Using a sputtering or electroplating method to form a working electrode layer at the position of the working electrode pattern using the target metal material to be tested; Removing the residual second semiconductor photoresist and metal material to obtain the working electrode; Applying a third semiconductor photoresist to the side of the first silicon substrate having the recessed portion and performing a third soft bake, and then using an auxiliary electrode mask to perform exposure, development, and dissolution under corresponding ultraviolet light to form an auxiliary electrode pattern; Using a sputtering or electroplating method to form an auxiliary electrode layer at the position of the auxiliary electrode pattern on the target metal material to be tested; Removing the residual third semiconductor photoresist and metal material to obtain the auxiliary electrode; that is, obtaining the working electrode-auxiliary electrode module; A reference electrode layer is provided on one side surface of the second silicon substrate by sputtering or electroplating, and then a fourth semiconductor photoresist is coated and a fourth soft bake is performed, and then an auxiliary electrode mask is used to expose, develop, and dissolve under corresponding ultraviolet light to form a reference electrode pattern; etching at the position of the reference electrode pattern by ion etching to remove the remaining fourth semiconductor photoresist and metal material to obtain the reference electrode; Coating a fifth semiconductor photoresist on a side of the second silicon substrate away from the reference electrode and performing a fifth soft bake, and then using a through hole mask to perform exposure, development, and dissolution under corresponding ultraviolet light to form a through hole pattern; The through hole is obtained by etching at the position of the through hole pattern by ion etching, that is, the reference electrode module is obtained; The working electrode-auxiliary electrode module and the reference electrode module are silicon-silicon bonded to obtain the MEMS-based material corrosion electrochemical measurement sensor.
6. The method for preparing a material corrosion electrochemical measurement sensor based on MEMS according to claim 5, characterized in that: The first silicon substrate and the second silicon substrate are cleaned before use.
7. The method for preparing a material corrosion electrochemical measurement sensor based on MEMS according to claim 5, characterized in that: The temperatures of the first soft baking, the second soft baking, the third soft baking, the fourth soft baking and the fifth soft baking are independently 90-110° C.
8. The method for preparing a material corrosion electrochemical measurement sensor based on MEMS according to any one of claims 5 to 7, characterized in that: Before the silicon-silicon bonding, cleaning the surfaces of the first silicon substrate and the second silicon substrate; The silicon-silicon bonding is performed by heating and annealing.
9. A material corrosion electrochemical measurement device, characterized in that: A MEMS-based material corrosion electrochemical measurement sensor comprising any one of claims 1-4.
10. The electrochemical material corrosion measuring device according to claim 9, characterized in that: Also included is a substrate lead frame; The working electrode, the auxiliary electrode, and the reference electrode are electrically connected to the substrate lead frame.
Citation Information
Patent Citations
Electrochemical sensor with opening between solid elements
CN109564182A
Monitoring method for atmospheric corrosion of metal component
CN109612920A
MEMS-based electrochemical gas sensor and preparation method thereof
CN113916950A
A miniaturised electrochemical sensor
EP2757367A1
Method for manufacturing high sensitive hybrid sensor chip for sensing heavy metal in water and portable water quality monitoring apparatus using the same
KR101525526B1